2012
DOI: 10.1128/aac.00481-12
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic Effect of Vitamin B 12 on Trypanosoma cruzi

Abstract: A nutritional characteristic of trypanosomatid protozoa is that they need a heme compound as a growth factor. Because of the cytotoxic activity of heme and its structural similarity to cobalamins, we have investigated the in vitro and in vivo effect of vitamin B 12 (or cyanocobalamin) on the different forms of Trypanosoma cruzi. Cyanocobalamin showed a marked antiparasitic activity against epimastigotes (50% inhibitory concentration [IC 50 ], 2.42 M), amastigotes (IC 50 , 10.69 M), and trypomastigotes (IC 50 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…Another recent study suggests that the combined use of gentian violet, ascorbic acid, and light to sterilize blood infected with Trypanosoma cruzi effectively prevents transfusion-based transmission of Chagas disease 3 . Other similar, recent data suggest that vitamin B12 may be of clinical value in the treatment of Chagas disease; vitamin B12 activity against trypomastigotes and epimastigotes is particularly significant 4 . Vitamin B12 mediates this anti-parasitic role by accentuating superoxide dismutase activity, which leads to augmented intracellular production of reactive oxygen species.…”
Section: Lettermentioning
confidence: 83%
“…Another recent study suggests that the combined use of gentian violet, ascorbic acid, and light to sterilize blood infected with Trypanosoma cruzi effectively prevents transfusion-based transmission of Chagas disease 3 . Other similar, recent data suggest that vitamin B12 may be of clinical value in the treatment of Chagas disease; vitamin B12 activity against trypomastigotes and epimastigotes is particularly significant 4 . Vitamin B12 mediates this anti-parasitic role by accentuating superoxide dismutase activity, which leads to augmented intracellular production of reactive oxygen species.…”
Section: Lettermentioning
confidence: 83%
“…Marim et al 5 have recently reported that vitamin C administration reduced parasitemia, although no effect was observed regarding the number of amastigote nets in the other tissues 6 . This phenomenon might limit the effi cacy of the combined treatment in the chronic phase, as other researchers have reported no statistically signifi cant histopathological differences in chronically infected mice that were treated with vitamin C for 180 days 7 .…”
Section: Dear Editormentioning
confidence: 98%
“…As well, Ciccarelli et al 5 have demonstrated that cyanocobalamin markedly decreased the motility and growth rate of Trypanosoma cruzi epimastigotes, where its cytotoxic action is thought to occur through the generation of ROS. Moreover, ascorbate peroxidase activity is significantly increased by cyanocobalamin, and ascorbic acid is known to intensify the antiparasitic activity of cyanocobalamin.…”
mentioning
confidence: 93%
“…This mechanism of action is likely due to the well-known prooxidant effects of these compounds, which, when combined with transition metal ions (Co, Cu, and Fe), generate ROS 6 . Accordingly, in the study of Ciccarelli et al 5 , the antiparasitic effect of Bnz treatment was further enhanced by the coadministration of cyanocobalamin and ascorbic acid. As well, it has previously be reported that the that treatment of blood infected with Trypanosoma cruzi with ascorbic acid, light, and gentian violet effectively prevents transmission of Chagas disease 7 .…”
mentioning
confidence: 99%